Bordered Writers : Latinx Identities and Literacy Practices at Hispanic-Serving Institutions - Murphy, Susan Wolff; Hinojosa, Yndalecio Isaac, 1971-; Baca, Isabel, 1965- (Book collections on Project MUSE., 2019)
Bordered writers explores how writing program administrators and faculty at Hispanic-Serving Institutions (HSIs) are transforming the teaching of writing to be more inclusive and foster Latinx student success. Like its 2007 predecessor, Teaching writing with Latino/a students, this collection contributes to ongoing conversations in writing studies about multicultural pedagogy and curriculum, linguistic diversity, and supporting students of color, while focusing further attention on the specific experiences and strategies of students and faculty at HSIs. Although members of Latinx communities comprise the largest underrepresented minority group in the nation, the needs and strength of Latinx writers in college classrooms are seldom addressed. Bordered writers thus helps to fill a critical gap, giving voice to past and present Latinx scholars, rhetoricians, and students, both in academic essays and in person testimonios, in four pivotal areas: developmental English and bridge programs, first-year writing, professional and technical writing, and writing centers and mentored writing. Across contributions, the collection strives to connect all bordered writers and educators, making higher education today not only stronger but also more representative of the nation's population.